EFEKTIFITAS PROGRAM DIKLAT BERJENJANG TINGKAT DASAR BAGI GURU PAUD DALAM JARINGAN DI KOTA DEPOK - Rosydiana, Erni; Dewi, Happy Indira; Winata, Widia (Instruksional, 2020)
This research is motivated by the qualifications of educators who have not been in line with expectations, lack of competence, lack of confidence in self-development, this is a condition that needs special attention and serious efforts. One effort was made in improving the quality of services for PAUD educators with the provision of training, namely tiered level training for PAUD teachers in the network. This study uses qualitative methods, especially naturalistic. The research analysis process follows the models of Miles and Huberman. The purpose of this study is to describe of the implementation of basic level education and training programs for PAUD teachers in the network, in addition to providing input into the basic level education and training program policies for PAUD teachers in the network. The process of collecting data using observation, interviews and documents. Data analysis includes analysis of data reduction, data display, and data verification. The results of the study show the effectiveness of the implementation of a basic level training program for PAUD teachers in a network in the city of Depok in the hope that it can be useful for relevant parties who can use such as principals, teachers, administrators, admin, mentors and further researchers.